Permafrost sensitivity to global warming of 1.5 °C and 2 °C in the Northern Hemisphere. (26th February 2021) - Liu, Lei; Zhao, Dongsheng; Wei, Junqi; Zhuang, Qianlai; Gao, Xuan; Zhu, Yu; Zhang, Jiacheng; Guo, Caiyun; Zheng, Du
Abstract: Permafrost degradation induced by climate warming is widely observed in the Northern Hemisphere. However, changes in permafrost sensitivity to climate warming (PSCW) in the future remains unclear. This study examined the changes in permafrost distribution in the Northern Hemisphere under global warming of 1.5 °C and 2 °C, and then characterized the spatial and temporal characteristics of PSCW. Global warming of 1.5 °C and 2 °C would result in 17.8 ± 5.3% and 28.3 ± 7.2% degradation of permafrost area under the climate scenario of Representative Concentration Pathway (RCP) 4.5, respectively, and 18.7 ± 4.6% and 28.1 ± 7.2% under the RCP 8.5, respectively. Permafrost tends to be more sensitive to climate change under the RCP 8.5 than RCP 4.5. PSCW shows small temporal variations in the 21st century under both RCPs, indicating a relatively stable sensitivity to warming on a hemisphere scale. However, PSCW varies greatly among regions, with high values at low latitudes and low values towards high latitudes. Air temperature is a major cause for the spatial heterogeneity of PSCW, explaining 66% of its variations. Permafrost under a warmer climate scenario tends to be more sensitive to the warming. Reducing snow depth and rising air temperature collectively enhances the permafrost sensitivity. Increasing in soil water content, by contrast, reduces the effect of warming. Permafrost in the south of the Northern Hemisphere is most vulnerable to climate warming. Our study highlights that permafrost in the region will respond differently under different warming scenarios across space (e.g. north vs south) and time (e.g. summer vs winter) in this century.